The Metropolitan Opera’s 50th Anniversary Gala: A Conversation with Robert Sutherland, Chief Librarian - Lo, Patrick; Sutherland, Robert (CAML Review / Revue de l’ACBM, 2018)
In an interview with Patrick Lo, Robert Sutherland, Chief Librarian of the Metropolitan Opera, describes the work carried out by the organization’s library staff in preparation for the Met’s 50th Anniversary Gala.